All about CDR transporters: Past, present, and future. Issue 4 (29th October 2018) - Prasad, Rajendra; Balzi, Elisabetta; Banerjee, Atanu; Khandelwal, Nitesh Kumar
Abstract: Drug resistance mechanisms in human pathogenic Candida species are continually evolving. Over the time, Candida species have acquired diverse strategies to vanquish the effects of various classes of drugs thereby, emanating as a serious life threat. Apart from the repertoire of well‐established strategies, which predominantly comprise alteration, overexpression of drug targets, and chromosome duplication, Candida species have evolved a number of permeability constraints for antifungal drugs, via compromised drug import or increased drug efflux. For the latter, genome of Candida species harbour battery of exporters designated as Candida drug resistance genes. These genes predominantly encode membrane efflux transporters, which expel the incoming drugs and thus prevent toxic intracellular accumulation of drugs to manifest multidrug resistance. Such a phenomenon is restricted not only to Candida species but has been observed among many other pathogenic fungal species as well. Notably, the existence of large number of drug exporters in genomes of Candida species posits other pivotal roles for these efflux transporter proteins. The brief review discusses as to how the whole gamut of antifungal research has since been changed to include these new observations wherein reduced permeability of azoles across cell membrane of Candida cells is being implicated as one of the major determinants of antifungal susceptibilities, which all began with the identification of the first multidrug resistance gene CDR1, in Andre Goffeau's laboratory back in 1995.